Histological percutaneous diagnosis of stage IV microcystic serous cystadenocarcinoma of the pancreas. (30th January 2013) - Bassam, Abu-Wasel; Keough, Valerie; Huang, Weei-Yuan; Molinari, Michele
Abstract : Malignant serous cystic neoplasms (SCN) of the pancreas are exceptionally rare, and only a few cases have been reported. As a result, SCN have been unanimously classified as benign tumours. Contrary to this conviction, in 1989, George et al published the very first case of a patient found to have a malignant pancreatic SCN. Up to the time of the submission of this paper, 27 cases of serous cystoadenocarcinomas have been published. In all the previously published cases of malignant SCN, the correct diagnosis was made postoperatively or at the time of autopsy. The authors present a case of a 68-year-old patient who was incidentally found to have a large liver mass on transthoracic echocardiogram ordered for suspected coronary artery insufficiency. Subsequent investigations revealed an additional large mass in the pancreas and percutaneous biopsies of both lesions revealed histological features consistent with malignant SCN metastasised to the left hepatic lobe.